2005
DOI: 10.1086/431501
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile and Burden of Rotavirus Diarrhea in Vietnam: 5 Years of Sentinel Hospital Surveillance, 1998–2003

Abstract: For 5 years, we have conducted sentinel surveillance for rotavirus at 6 hospitals in 4 cities in Vietnam. Stool samples obtained from >10,000 children <5 years old who were admitted to the hospital with diarrhea have been screened for rotavirus. Overall, 55% of samples were positive, and there was little variability in rates of detection of rotavirus between sites (44%-62%). In Vietnam, the characteristics of rotavirus infection more closely resemble those seen in developed countries, rather than those seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 8 publications
(11 reference statements)
2
16
1
Order By: Relevance
“…Genotype G2 was not identified and has not been documented for over 8 years in Kenya as documented by Kiulia et al [34]. The current study did not document any case of G1 genotype among vaccinated children although numerous molecular epidemiological studies have indicated that G1 is the most common circulating G type around the world [37, 49, 50]. Interestingly none of the specimens processed demonstrated genotype P [8].…”
Section: Discussioncontrasting
confidence: 45%
“…Genotype G2 was not identified and has not been documented for over 8 years in Kenya as documented by Kiulia et al [34]. The current study did not document any case of G1 genotype among vaccinated children although numerous molecular epidemiological studies have indicated that G1 is the most common circulating G type around the world [37, 49, 50]. Interestingly none of the specimens processed demonstrated genotype P [8].…”
Section: Discussioncontrasting
confidence: 45%
“…Additionally, another monovalent human rotavirus vaccine, Rotavin-M1, was manufactured in Vietnam and licensed in 2012. Rotavin-M1 promises to be effective in reducing the number of rotavirus diarrhea in Vietnam that accounted for more than 50% of diarrheal hospitalizations and 5,300–6,800 deaths in children less than 5 years of age annually [5]. However, recent studies conducted in Mexico and Brazil showed that there was an increased risk of intussusception associated with the use of rotavirus vaccines [6].…”
Section: Introductionmentioning
confidence: 99%
“…The report of surveillance showed that rotavirus infection explains for up to 55 -60 % of the hospitalized cases of diarrheal illness in infants and young children [1 -3]. Estimated by WHO, 20 % of deaths in children under 5 years old was due to rotavirus infection [3,4]. These factors make it necessary to develop a diagnostic system that permits the specific detection of rotavirus [5].…”
Section: Introductionmentioning
confidence: 99%